Analisis Tingkat Pelayanan Atas Kepuasaan Pelanggan Penyedia Barang Logistik Yang Akan Di Asuransikan Pada PT Kereta Api (Persero ) Medan Labuhan - Ashaari , Taslam; Batubara, Maryam (Universitas Pahlawan Tuanku Tambusai, 2024)
The level of customer satisfaction with logistics goods provider services, especially PT Kereta Api (Persero) Medan Labuhan, is the main focus in this analysis. Through a survey of 35 respondents using local and long-distance train services, six main aspects of service were evaluated: ticket sales service, arrival time, cabin cleanliness, security, air circulation, and arrival time at destination. The results illustrate that despite improvements in some aspects, such as arrival times and safety, additional areas, including cabin cleanliness and air circulation, still have plenty of space for further development. According to these results, if we want to make train travel better for everyone, we need to pay close attention to these elements.